Functional Analysis of Human and Feline Coronavirus Cross-Reactive Antibodies Directed Against the SARS-CoV-2 Fusion Peptide - Vanderheijden, Nathalie; Stevaert, Annelies; Xie, Jiexiong; Ren, Xiaolei; Barbezange, Cyril; Noppen, Sam; Desombere, Isabelle; Verhasselt, Bruno; Geldhof, Peter; Vereecke, Nick; Stroobants, Veerle; Oh, Dayoung; et al. (Frontiers in Immunology, 2022)
To face the continuous emergence of SARS-CoV-2 variants, broadly protective therapeutic antibodies are highly needed. We here focused on the fusion peptide (FP) region of the viral spike antigen since it is highly conserved among alpha- and betacoronaviruses. First, we found that coronavirus cross-reactive antibodies are commonly formed during infection, being omnipresent in sera from COVID-19 patients, in ~50% of pre-pandemic human sera (rich in antibodies against endemic human coronaviruses), and even in feline coronavirus-infected cats. Pepscan analyses demonstrated that a confined N-terminal region of the FP is strongly immunogenic across diverse coronaviruses. Peptide-purified antibodies targeting this FP region exhibited broad binding of alpha- and betacoronaviruses, besides weak SARS-CoV-2 neutralizing activity. The apparent presence of a cryptic neutralizing epitope in this highly conserved N-terminal part of the FP makes it a highly relevant target for designing therapeutic antibodies with broad coronavirus coverage, including variants.